1995
DOI: 10.1073/pnas.92.5.1327
|View full text |Cite
|
Sign up to set email alerts
|

Development of anti-p185HER2 immunoliposomes for cancer therapy.

Abstract: The product of the HER2 protooncogene, p185HEP2, represents an attractive target for cancer immunotherapies. We The HER2 (c-erbB2, neu) protooncogene and pl85HER2, the growth factor receptor-tyrosine kinase it encodes, appear to play a central role in the pathogenesis of many human cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(130 citation statements)
references
References 18 publications
7
123
0
Order By: Relevance
“…As expected, on EpCAM-negative RL cells, no difference in cell binding and inhibition of proliferation was observed for EpCAM-targeted and nontargeted liposomes. These results are in line with previous reports showing that the uptake of targeted liposomes by receptor-mediated endocytosis is obligatory for the cytotoxicity of encapsulated drugs (31,36,47).…”
Section: Discussionsupporting
confidence: 83%
“…As expected, on EpCAM-negative RL cells, no difference in cell binding and inhibition of proliferation was observed for EpCAM-targeted and nontargeted liposomes. These results are in line with previous reports showing that the uptake of targeted liposomes by receptor-mediated endocytosis is obligatory for the cytotoxicity of encapsulated drugs (31,36,47).…”
Section: Discussionsupporting
confidence: 83%
“…Fax: (1) (415) 617-3080. E-mail: SAMUEL@SEQUUS.com Abbreviations: CHEMS, cholesteryl hemisuccinate; Chol, cholesterol; DOPC, 1,2-dioleoyl-sn-glycerophosphorylcholine; DOPE, 1,2-dioleoyl-sn-glycero-3-phosphorylethanolamine; DPX, p-xylene-bis-pyridinium bromide; DSPE, 1,2-distearoyl-sn-glycero-3-phosphorylethanolamine; DTSP, dithiobis(succinimidyl propionate); DTT, dithiothreitol; HEPES-NS, 20 mM N-hydroxyethyl-piperazinoethanesulfonic acid, 144 mM NaCI, pH 7.2; HPTS, trisodium 8-hydroxypyrenetrisulfonate; MES, N-morpholinoethanesulfonic acid; NBD-PE, N-(7-nitro-2-1,3-benzoxadiazol-4-yl)-phosphatidylethanolamine (egg transphosphatidylated); PEG, poly(ethylene glycol); mPEG, methoxypoly(ethylene glycol); mPEG-DSPE, N-(c0-methoxypoly(oxyethylene)-a-oxycarbonyl)-DSPE; mPEG-DTP-DSPE, N-(2-(~-methoxypoly(oxyethylene)-a-aminocarbonyl)ethyl-dithiopropionyl)-DSPE; mPEG-DTP-OSu, N-succinimidyl-(2-(o)-methoxypoly(oxyethylene)-c~-aminocarbonyl)ethyl-dithiopropionate; PL, phospholipid; Rho-PE, Nlissamine-rhodamine B sulfonyl-phosphatidylethanolamine (egg transphosphatidylated); RES, reticuloendothelial system; SSL, sterically stabilized liposomes uptake by target cells is observed [5][6][7]. However, grafting of PEG on the liposome surface interferes with the ability of the liposome to undergo membrane fusion and destabilization [8] which are important mechanisms for making SSL-carried pharmaceuticals available to their biological targets.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] It has been reported that anti-HER-2 monoclonal antibody Fab 0 fragments conjugated to liposomes bind specifically to breast cancer cell line SK-BR-3 overexpressing the HER-2/neu (EFG receptor), resulting in enhanced internalization of the liposomes. 14,34 More recently, there have been a number of studies that utilized antibodies against tumor-associated antigens coupled to liposomes to target tumor cells for delivery of genes and drugs. 14,20,[34][35][36] In this study, we conjugated Fab 0 fragments of humanized anti-TAG-72 antibodies (HuCC49) to liposomes encapsulating pDNA for tumor-directed gene delivery.…”
Section: Discussionmentioning
confidence: 99%
“…14,34 More recently, there have been a number of studies that utilized antibodies against tumor-associated antigens coupled to liposomes to target tumor cells for delivery of genes and drugs. 14,20,[34][35][36] In this study, we conjugated Fab 0 fragments of humanized anti-TAG-72 antibodies (HuCC49) to liposomes encapsulating pDNA for tumor-directed gene delivery. The Fab 0 fragments retained the capability of specific binding to TAG-72 expressed on LS174 T tumor cells.…”
Section: Discussionmentioning
confidence: 99%